Can Intensive Care For Extremely Premature Infants Be Defended? A Critical Review - Seaman, Jade (2013)
Background: Advances in medical technology throughout the twentieth century have resulted in younger and smaller premature babies being kept alive. Improvements can be seen in survival rates of babies as young as 26 weeks; however this same improvement cannot be seen in babies of 24 weeks or younger, suggesting that the limit of viability has been reached. Aim: As babies of a younger gestational age are being admitted to neonatal units for intensive care, should we be asking if the limit of viability has been pushed too far? This study aims to investigate whether intensive care for these extremely premature infants can be defended. Method: This dissertation uses a critical review methodology. Summary of findings: Ethical dilemmas face healthcare professionals and parents everyday within the neonatal intensive care unit. In order to provide care that is in the best interests of the patient all options should be carefully considered. Human embryological development shows us that prematurity affects many of the vital body systems, as the majority of maturation occurs in the third trimester of pregnancy. Findings of the EPICure studies, observational cohort studies, show that although survival rates for extremely premature infants have improved, the same cannot be said for the rates of disability and other impairments in later life. It is essential that all statistics and information is laid out and presented to parents in a way that is easily understandable so informed decisions can be made for these tiny babies. Conclusion: Intensive treatment for premature infants below 24 weeks of gestation cannot be defended. For those 24 weeks of gestational age or over intensive treatment may not always be appropriate; instead comfort care should be considered a viable option.